استدلال بالحدیث کے متعلق حنفیہ کے بنیادی اصول: THE FUNDAMENTAL PRINCIPLES OF THE HANAFI JURISPRUDENCE REGARDING INFERENCE FROM HADITH (Al-Aasar, 2025)
This paper elucidates the foundational principles (Uṣūl) of the Ḥanafī School of jurisprudence concerning Ḥadīth interpretation, aiming to rectify the common misconception that it prioritizes analogical reasoning (Qiyās) over prophetic traditions. It argues that the Ḥanafī School employs a distinct, coherent, and text-centric methodology for Ḥadīth criticism, which should be evaluated within its own conceptual framework. Key principles examined include the preference for a narrator’s jurisprudential insight (Fiqāhah) over mnemonic strength (Ḥifẓ) in cases of conflicting reports. The study highlights that a Ḥadīth with an authentic chain of narration (Isnād) may be deemed inapplicable if it contradicts higher-order textual sources such as the Qurʾān, the well-established Sunnah, or fundamental legal principles like those governing matters of widespread public involvement (ʿUmūm al-Balwá). Crucially, the paper underscores the foundational Ḥanafī maxim that a weak (Ḍaʿīf) or Mursal (discontinuous chain) Ḥadīth is considered a stronger legal source than Qiyās. This principle directly challenges the stereotype of the Ḥanafīs as “people of opinion” (Ahl al-Raʾy). In conclusion, the research demonstrates that the Ḥanafī legal system is internally consistent. Apparent deviations from a given Ḥadīth are not arbitrary but result from a sophisticated hermeneutical framework. A fair scholarly assessment of Ḥanafī jurisprudence is, therefore, contingent upon an appreciation of its unique Uṣūl.